2023
DOI: 10.3390/ma16051916
|View full text |Cite
|
Sign up to set email alerts
|

A Numerical Study of Crack Mixed Mode Model in Concrete Material Subjected to Cyclic Loading

Abstract: In quasi-brittle materials such as concrete, numerical methods are frequently used to simulate the crack propagation for monotonic loading. However, further research and action are required to better understand the fracture properties under cyclic loading. For this purpose, in this study, we present numerical simulations of mixed-mode crack propagation in concrete using the scaled boundary finite element method (SBFEM). The crack propagation is developed based on a cohesive crack approach combined with the the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Second, the uncertainty analysis regarding those issues worth further pursuing with quantitative analysis, as comprehensively examining variou SCB test settings in former studies [31]. Third, as this study narrowed down the researc focus merely on mixed-mode fracturing (types I and II) for SCB tests on chevron notc disks having sharp tips instead of a straight-through notch, many other influencing fa tors, such as the effects of aggregate size [42], cyclic loading [43], another mixed-mod fracturing (types I and III) [44], etc., have not been sufficiently considered at the initi However, those criteria are applicable mostly for homogeneous brittle materials such as glass, rock, and concrete without reinforcement. Razmi and Mirsayar [40] and Karimzadeh, et al [41] used SCB tests to investigate mixed-mode (types I and II) fractures in concrete SCCND specimens reinforced with fibers.…”
Section: Limitations and Prospectsmentioning
confidence: 98%
See 1 more Smart Citation
“…Second, the uncertainty analysis regarding those issues worth further pursuing with quantitative analysis, as comprehensively examining variou SCB test settings in former studies [31]. Third, as this study narrowed down the researc focus merely on mixed-mode fracturing (types I and II) for SCB tests on chevron notc disks having sharp tips instead of a straight-through notch, many other influencing fa tors, such as the effects of aggregate size [42], cyclic loading [43], another mixed-mod fracturing (types I and III) [44], etc., have not been sufficiently considered at the initi However, those criteria are applicable mostly for homogeneous brittle materials such as glass, rock, and concrete without reinforcement. Razmi and Mirsayar [40] and Karimzadeh, et al [41] used SCB tests to investigate mixed-mode (types I and II) fractures in concrete SCCND specimens reinforced with fibers.…”
Section: Limitations and Prospectsmentioning
confidence: 98%
“…Second, the uncertainty analysis regarding those issues is worth further pursuing with quantitative analysis, as comprehensively examining various SCB test settings in former studies [31]. Third, as this study narrowed down the research focus merely on mixed-mode fracturing (types I and II) for SCB tests on chevron notch disks having sharp tips instead of a straight-through notch, many other influencing factors, such as the effects of aggregate size [42], cyclic loading [43], another mixed-model fracturing (types I and III) [44], etc., have not been sufficiently considered at the initial stage of this study and should, therefore, be further investigated in the future works. Last, the other numerical method, the discrete element method (DEM) [45], can be additionally involved in future numerical modelling mixed-mode fracturing behavior to explore the dependence of different numerical methods.…”
Section: Limitations and Prospectsmentioning
confidence: 99%
“…Kousa [ 17 ] concluded that the coupling effect has a synergistic effect on the durability degradation of concrete by simulating the durability degradation of concrete in the natural environment; the overall degradation process of concrete durability can be predicted quantitatively. Alrayes [ 18 ] presented numerical simulations of mixed-mode crack propagation in concrete using the scaled boundary finite element method. However, the deterioration of concrete durability is caused by the coupling of many factors, and it is a constantly changing process in the service process of concrete structures.…”
Section: Introductionmentioning
confidence: 99%
“…A three-dimensional numerical method was proposed in Zhang et al (2023) to simulate the propagation process of the mode-I local defect in the concrete and the results showed that the local defect propagates alongside the thickness' direction and parallel to the upper bound-areas. A numerical simulation of mixed-mode defect propagation in concrete using the scaled boundary finite element method (SBFEM) and cohesive defect approach was studied in Alrayes et al (2023). The proposed method investigated defect growth propagation and dam-age accumulation for cyclic loading within the SBFEM framework.…”
Section: Introductionmentioning
confidence: 99%